Optimum power of low-temperature plasma selectivity for human melanoma cell treatment - Sarut Chaisrisawadisuk (2019)
© 2019 by Begell House, Inc. www.begellhouse.com. The number of new cases of melanoma is increasing every year. Due to its specific-ity of treatment, plasma medicine has been claimed to be a novel adjunctive procedure. We evalu-ated the effects of a direct low-temperature plasma (LTP) device for selective tumor eradication, comparing between melanoma and normal keratinocyte cell lines. Human melanoma (G-361) and normal keratinocyte (HaCaT) cell lines were subjected to LTP treatment. Different powerlevels and exposure durations of LTP were compared in both groups. After the treatment, a MTT assay was used to determine cell viability. The physical plasma characteristics of the three powers were also evaluated. It was found that low power (intensity 1 with frequency 10 Hz) was 0.25 watts, while medium power (intensity 5 with frequency 50 Hz) and high power (intensity 10, with frequency 100 Hz) were 0.94 and 3.0 watts, respectively. Higher powers and longer durations of LTP treatment increased the incidence of cell death in both the HaCaT and G-361 cell lines. LTP eliminated slightly more G-361 than HaCaT cells at 10 and 30 seconds of exposure. At 60 seconds or more, LTP showed a decrease of more than 50% in both the HaCaT and G-361 survival. Medium LTP power with 10-second exposure demonstrated a statistically significant differencebetween HaCaT and G-361 viabilities (77.1% and 66.3%, respectively; P = 0.01). LTP treatment at medium power (intensity 5 with frequency 50 Hz, equal to 0.94 watts) at 10-second duration showed a specificity for cancer eradication.